2013
DOI: 10.5114/pg.2013.36327
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nutritional treatment on immune function

Abstract: K Ke ey y w wo or rd ds s: : immunonutrition, acute pancreatitis, perioperative therapy, sepsis. S Sł ło ow wa a k kl lu uc cz zo ow we e: : immunożywienie, ostre zapalenie trzustki, terapia okołooperacyjna, sepsa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…As is generally known, malnutrition is also one of the aetiological factors in immunocompromised patients, predisposing them to infectious lesions [ 18 ]. The immunodeficiency level in patients with liver failure depends on a number of factors, including underlying diseases, treatment (immunosuppressants, glucocorticoids) as well as the level of organ impairment (malnutrition, cholestasis) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…As is generally known, malnutrition is also one of the aetiological factors in immunocompromised patients, predisposing them to infectious lesions [ 18 ]. The immunodeficiency level in patients with liver failure depends on a number of factors, including underlying diseases, treatment (immunosuppressants, glucocorticoids) as well as the level of organ impairment (malnutrition, cholestasis) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 That said, a large body of evidence also points to the effects of these vitamins on lymphocyte activity and differentiation. 19 Effects on differentiation will, in turn, lead to alterations in the profile of cytokines produced by T cells with ensuing pathogenic and protective effects. Indeed, Dawson et al have reported that the in vitro treatment of human peripheral blood mononuclear cells (PBMCs) with vitamin A can downregulate IFNγ, IL-2, IL-12p70, and TNF-α levels and enhance the expression and IL-4, IL-5, and IL-13, all associated with elevated TH2 transcription factor expression GATA3.…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of the treatment of patients with chronic pancreatitis is also an adequate supply of pancreatic enzymes and vitamins B, A, D, E, and K and folic acid supplementation [ 7 , 8 ]. The nutritional therapy should include also nutrients with confirmed regulatory effects on the immune system like: saturated amino acids (arginine), unsaturated amino acids (glutamine, glycine), sulphur amino acids, nucleotides, polyunsaturated fatty acids (ω-3, ω-6), antioxidants (vitamin C, vitamin E, β-carotene), and trace elements (selenium, copper, zinc, iron) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%